2013
DOI: 10.1111/pcmr.12172
|View full text |Cite
|
Sign up to set email alerts
|

Why is melanoma so metastatic?

Abstract: Summary Malignant melanoma is one of the most aggressive cancers and can disseminate from a relatively small primary tumor and metastasize to multiple sites, including the lung, liver, brain, bone, and lymph nodes. Elucidating the molecular and genetic changes that take place during the metastatic process has led to a better understanding of why melanoma is so metastatic. Herein, we describe the unique features that distinguish melanoma from other solid tumors and contribute to the malignant phenotype of melan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
130
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 168 publications
(200 reference statements)
0
130
0
3
Order By: Relevance
“…It indeed has been shown that melanoma cells that have the ability to detach from the primary tumor and intravasate into blood or lymphatic vessels, have many antigens in common with vascular endothelial cells, such as melanoma cell adhesion molecules, N-cadherin, vascular cell adhesion molecule, intracellular adhesion molecule, platelet endothelial cell adhesion molecule and vascular endothelial-cadherin, allowing melanoma cells to survive the physical forces within the circulation, adhere to the vessel wall within distant organs, and extravasate into the parenchyma. 28,29 The second possible reason is that because of the inclusion criteria (available histological material), most of the included patients presented with large and extensive SLN metastasis with expected high oxygen and nutrient needs, justifying the highly angiogenic phenotype of metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…It indeed has been shown that melanoma cells that have the ability to detach from the primary tumor and intravasate into blood or lymphatic vessels, have many antigens in common with vascular endothelial cells, such as melanoma cell adhesion molecules, N-cadherin, vascular cell adhesion molecule, intracellular adhesion molecule, platelet endothelial cell adhesion molecule and vascular endothelial-cadherin, allowing melanoma cells to survive the physical forces within the circulation, adhere to the vessel wall within distant organs, and extravasate into the parenchyma. 28,29 The second possible reason is that because of the inclusion criteria (available histological material), most of the included patients presented with large and extensive SLN metastasis with expected high oxygen and nutrient needs, justifying the highly angiogenic phenotype of metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…We were curious what would occur to DNA methylation patterns of cells that disseminate from the primary location and colonize in metastatic sites. To evaluate this, we focused on melanoma, a highly metastatic cancer (Braeuer et al 2014). We compared methylation data from metastatic melanoma patients (seven distinct locations) to data from patients with primary in situ melanoma (Supplemental Table S1).…”
Section: Accumulation Of Edmr Hypomethylation Correlates With Likelihmentioning
confidence: 99%
“…Its aggressiveness is based on the highly metastatic potential of melanoma cells, which can still not be efficiently targeted despite recent progress in melanoma therapies 2 . In fact, currently available drugs frequently induce resistance 3 and have even been shown to promote invasiveness and metastasis of resistant cells 4 .…”
mentioning
confidence: 99%